The Food Immunology for Asthma Patients - Ibrahim, Nur Aifiah Binti (Budapest International Research in Exact Sciences (BirEx) Journal, 2026)
Diet can alter the immune bodily functions for its pro-inflammatory response. Another chapter for the stool and wastes to be in a healthy state. The keto diet is a refinery process for fibres and vegetables to reduce acidity and achieve the optimum level in achieving a high body standard. The food test tube is for the measurement of portion and a colorful dietary pattern. The most leafy vegetables are the least, and the most darker ones are for the digestive gut. The taste buds have enough pleasure in seeking the tastiness and depth of flavours. There is a food sensibility in rationalizing the time of the phase for the reactivity to take place in the body clock.